Engineering low intensity planar textures in commercial purity nickel sheets by cross roll bonding - Duan, J.; Quadir, Md Zakaria; Ferry, M. (Elsevier BV, 2017)
© 2016 Elsevier B.V. Accumulative roll bonding is a severe plastic deformation technique capable of generating nano-scale microstructures in sheet metals. This technique can also be exploited for processing novel sheet products that are not possible through conventional rolling. In this investigation, cross rolling was combined with accumulative roll bonding of commercial purity nickel sheets, for obtaining an overall reduction in intensity of the deformation and recrystallization textures, which has been a long-time objective for obtaining drawable face centred cubic metal sheet. Overall, a significant reduction in the texture intensities were achieved by incorporating cross roll bonding. In particular, the dominance of the cube texture component, which readily forms in heavily cold rolled and annealed high stacking fault energy, face centred cubic metals and alloys, was suppressed by adopting this processing route. Texture-based Schmidt factor calculations points to a significant reduction in planar anisotropy of the cross rolled and annealed sheet, which is an important factor governing the earing propensity of deep drawn cups.